Analytical Model: Characteristics of Nanosecond Pulsed Plasma Synthetic Jet Actuator in Multiple-Pulsed Mode (Advances in Applied Mathematics and Mechanics, 2018)
Multi-field coupling simulation method based on the physical principles isused to simulate the discharge characteristics of nanosecond pulsed plasma syntheticjet actuator. Considering the effect of the energy transferring for air, the flow characteristicsof nanosecond pulsed plasma synthetic jet actuator are simulated. The elasticheating sources and ion joule heating sources are the two main sources of energy.Through the collisions, the energy of ions is transferred to the neutral gas quickly. Theflow characteristics of a series of blast waves and the synthetic jet which erupt from theplasma synthetic jet (PSJ) actuator are simulated. The blast wave not only promotesoutward, but also accelerates the gas mixing the inhaled gas from the outside cavitywith the residual gas inside the cavity. The performances of PSJ actuator fluctuate inthe first three incentive cycles and become stable after that.